IMPLEMENTASI METODE SIX SIGMA PADA USAHA UMKM CATERING NYEBLAK SPOT TERHADAP KECACATAN PRODUK - Salsabila, Nada Fara; Nurmala, Zahwa Auliya; Sitohang, Esra; Kamil, Zuhdi; Madyanti, Aniza Nur (Journal of Social Science and Multidisciplinary Analysis, 2025)
This study aims to analyze and improve the quality process of the MSME catering business "Nyeblak Spot," which faces two main issues: delivery delays and product defects. To address these problems, the Six Sigma approach using the DMAIC (Define, Measure, Analyze, Improve, Control) methodology was applied. The measurement results show a DPMO of 33,997 for product defects with a sigma level of 2.31, and a DPMO of 208,791 for delivery delays with a sigma level of 4.84. The fishbone analysis reveals that the primary causes of product defects include the lack of SOPs and inconsistencies in packaging, while delays are due to a lack of delivery fleet and absence of a structured schedule. By implementing improvements focused on SOP development, staff training, and organized delivery scheduling, the business is expected to enhance operational efficiency and customer satisfaction. Keywords: Six Sigma, DMAIC, delivery delays, product defects, catering MSMEs.